SEXUAL CONTINENCE AND MASCULINE TRAGEDY IN SOYINKA’S DEATH AND THE KING’S HORSEMAN (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
Wole Soyinka’s play, Death and The King’s Horseman, occupies a pride of place in Africa’s literary provenance given its inevitable imbrication of multiple humanistic and artistic categories such as history, clash of cultures and gender peculiarities. However, the interpretive nuances of the play focus more on culture conflict between Western Eurocentric modernist convictions and African traditional, historical realities. Although these cultural cross-currents have generated valid arguments and critical engagements of literary possibilities, they also initiate a tyranny of interpretation, shutting the door to other meanings in the text. Through a deconstructive prism, this study opens a new vista of meaning in the text. It argues that beyond the cultural tensions in the play, Soyinka experiments with sexuality, demonstrating that sex and its unending lure for ultimate gratification remains an essential part of man’s validation of masculinity. The playwright, using Elesin Oba the lead character, proves that a lack of sexual continence remains man’s Achilles Heels, constituting his biggest challenge towards the attainment of glory and fulfilment. Man’s constant capitulation before the altar of female sexuality remains a constant threat to his ascension to the pinnacle of his potential. Several masculine tragedies will be averted and abrogated if the existential threat posed by the feminine gender and sexuality is acknowledged and circumvented.
Keywords: Sexuality,Continence,MasculineTragedy,Essentialism,Deconstruction